The role of PET for interim response assessment in patients with Hodgkin’s lymphoma - Zaucha, Jan; Danielewicz, Iwona; Małkowski, Bogdan; Zaucha, Renata; Leśniewski-Kmak, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2009)
18F 2-fluoro-2-deoxyglucose positron emission tomography (FDG-PET) assessment after completion of therapy for lymphomas has been recently incorporated into the clinical guidelines and is also advocated in Poland by the National Health Fund. There is emerging evidence that in patients with Hodgkin’s lymphoma (HL) PET performed early during chemotherapy predicts the therapy response better than post-therapy PET. However, it is not clear which criteria should be adopted for an interim PET assessment because of minimal residual uptake (MRU), which hampers interpretation of PET scans as positive or negative. This brief review summarizes the evidence to date for the use of interim PET assessment in patients with advanced HL both using ABVD and BEACOPPesc chemotherapy. The rationale for performing an observational study in Poland aiming at defining criteria used for interim PET assessment which could be utilized in the future as a basis for early therapeutic modification in routine clinical practice is also discussed.